2014
DOI: 10.1117/12.2048231
|View full text |Cite
|
Sign up to set email alerts
|

Optical volumetric inspection of sub-20nm patterned defects with wafer noise

Abstract: We have previously introduced a new data analysis method that more thoroughly utilizes scattered optical intensity data collected during defect inspection using bright-field microscopy. This volumetric approach allows conversion of focusresolved 2-D collected images into 3-D volumes of intensity information and also permits the use of multi-dimensional processing and thresholding techniques to enhance defect detectability. In this paper, the effects of wafer noise upon detectability using volumetric processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, with the development of technology, improved optical simulations and new insights it was found that the out-of-focus TF images do contain useful information regarding the target being imaged. New applications and uses are being found for blurred optical images that were previously considered unusable (20, 29, 32, 34, 4348). The major challenge was to extract high quality, usable information from the blurred TF optical images.…”
Section: Significance Of Tf Image Collectionmentioning
confidence: 99%
“…However, with the development of technology, improved optical simulations and new insights it was found that the out-of-focus TF images do contain useful information regarding the target being imaged. New applications and uses are being found for blurred optical images that were previously considered unusable (20, 29, 32, 34, 4348). The major challenge was to extract high quality, usable information from the blurred TF optical images.…”
Section: Significance Of Tf Image Collectionmentioning
confidence: 99%